Hormone replacement therapy and quality of life of women in peri- and postmenopause - Żołnierczuk-Kieliszek, Dorota; Kulik, Teresa Bernadetta; Wiktor, Henryk; Pacian, Anna; Stefanowicz, Agata (Polish Journal of Public Health, 2010)
Aim. The aim of the research was to estimate if the women’s quality of life depends on present or past taking HRT. Material and methods. The survey was carried out by means of a survey method, a postal questionnaire technique. Three standardized questionnaires: the WHOQOL-BREF, the Women’s Health Questionnaire (WHQ) and the SF-36 were used as research tools. A self-constructed questionnaire was also put into use. The questionnaires were sent to a representative sample of 7,875 women between 45 and 65 years old, living in the Lublin province, in 2007. The mail addresses were obtained from the Local Data Bank of the Lublin Provincial Office. We received 2,143 replies (feedback 27.2 %). The statistical analysis of the obtained data has been performed. The domains of the quality of life defined by the WHOQOL, the WHQ and the SF-36 questionnaires were treated as dependent variables whereas the data on using HRT by women were treated as independent variables. Results. The positive impact on the quality of life of women taking HRT was not proved unambiguously. Women taking HRT in form of tablets revealed slightly better quality of life than women taking other forms of hormones. There were no statistical differences in the quality of life of women upon the duration of admitting HRT. The worse quality of life was found in women who quoted the appearance of HRT side effects and in women who were dissatisfied with the effects. The multivariate analysis showed that HRT admitting had an irrespective impact on women’s quality of life only in one domain – the domain of sleep problems of the WHQ questionnaire